Experience and Perceptions About Infographic With Educational Purposes in Teaching Training - Ríos-Higuera, Selenne; Caro-Coronado, Isis Berenice; Espinoza-Cid, Rosa Ascención (Revista Electrónica Educare, 2022)
Objective. This article presents the findings of a study that seeks to know the perceptions of a teacher and a group of student teachers from a Normal Superior School related to two experiences designing infographics for educational purposes. Methodology. This study was qualitative. The data was collected by implementing a focus group conformed by five students in their sixth semester and an interview with the teacher who implemented the strategy. Results. The findings suggest a positive perspective from both the teacher and the students regarding the experience of designing infographics. They declare it mainly contributed to the comprehension and organization of information, specifically providing comprehension of academic and disciplinary texts. In addition, the participants state that the design of infographics facilitates the organization of relevant information in a visual way, which proves to be innovative, creative, and useful for students in initial education. Conclusions and recommendations. Even though it is important to inquire about teachers and students’ perspectives on the use of infographics for educational purposes, it is recommended to conduct experimental or quasi-experimental studies which validate or refute the findings of this study and other similar studies which have been conducted from the perspectives of students and teachers.